The shariah, Islamic banks and accounting concepts - Muhammad Akhyar Adnan (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 1997)
It is widely questioned recently whether the current (conventional) accounting concepts and practices are Islamicly acceptables. some papers, thesis and books have been attempting to deal with this regard (eg Abdel-Magid, 1981; Fekrat, 1985; Ahmed, 1990, Gambling and Karim, 1991; to mention but few). More recently, a special institution which ius aimed to established a particular Islamic banks accounting standards had been establised. However, the issue of accounting and auditing viewed from Islamic perspective is still stimulating to discuss. What have been written by Muslim scholars has not been able to cease the discussion of accounting and auditing from Islamic point of view, not the issuance of Statement of Financeial Accounting by the Financial Accounting Organization for Islamic Banks and Financial Istitutions (FAO-IBFI). This paper is seeking to contribute some ideas based on those opinion, either of the Muslim scholars of accounting, or the formal standards publised by the FAO-IBFI.